Transorbital approach to the cavernous sinus: an anatomical study of the related cranial nerves - Mosteiro, Alejandra; Codes, Marta; Tafuto, Roberto; Manfrellotti, Roberto; Torales, Jorge; Enseñat, Joaquim; Di Somma, Alberto; Prats-Galino, Alberto (Frontiers in Neuroanatomy, 2024)
Background The cavernous sinus (CS) is a demanding surgical territory, given its deep location and the involvement of multiple neurovascular structures. Subjected to recurrent discussion on the optimal surgical access, the endoscopic transorbital approach has been recently proposed as a feasible route for selected lesions in the lateral CS. Still, for this technique to safely evolve and consolidate, a comprehensive anatomical description of involved cranial nerves, dural ligaments, and arterial relations is needed. Objective Detailed anatomical description of the CS, the course of III, IV, VI, and V cranial nerves, and C3-C7 segments of the carotid artery, all described from the ventrolateral endoscopic transorbital perspective. Methods Five embalmed human cadaveric heads (10 sides) were dissected. An endoscopic transorbital approach with lateral orbital rim removal, anterior clinoidectomy, and petrosectomy was performed. The course of the upper cranial nerves was followed from their apparent origin in the brainstem, through the middle fossa or cavernous sinus, and up to their entrance to the orbit. Neuronavigation was used to follow the course of the nerves and to measure their length of surgical exposure. Results The transorbital approach allowed us to visualize the lateral wall of the CS, with cranial nerves III, IV, V1-3, and VI. Anterior clinoidectomy and opening of the frontal dura and the oculomotor triangle revealed the complete course of the III nerve, an average of 37 (±2) mm in length. Opening the trigeminal pore and cutting the tentorium permitted to follow the IV nerve from its course around the cerebral peduncle up to the orbit, an average of 54 (±4) mm. Opening the infratrochlear triangle revealed the VI nerve intracavernously and under Gruber’s ligament, and the extended petrosectomy allowed us to see its cisternal portion (27 ± 6 mm). The trigeminal root was completely visible and so were its three branches (46 ± 2, 34 ± 3, and 31 ± 1 mm, respectively). Conclusion Comprehensive anatomic knowledge and extensive surgical expertise are required when addressing the CS. The transorbital corridor exposes most of the cisternal and the complete cavernous course of involved cranial nerves. This anatomical article helps understanding relations of neural, vascular, and dural structures involved in the CS approach, essential to culminating the learning process of transorbital surgery.